The functional model of contemporary educational partnership - Diana ANTOCI; Vasilica ANDRASCIUC BIRTOK (Acta et Commentationes, Sciences of Education, 2023)
The educational partnership carried out at any level of education, be it preschool, primary, secondary, high school, is essential for the personality’s development. An important aspect addressed in this article is the socialization process, carried out within the educational partnership, which is necessary for children, parents and teachers. The analysis of scientific sources allowed us to identify the structural components of the educational partnership and in the process of its realization it would be advisable to focus and take into account the following elements: communication, compliance, creativity, coherence, cohesion, efficiency. The evaluation and development of the partnership from the perspective of the nominated contents will ensure the achievement of the purpose and objectives put forward, the visibility of the expected results following the accomplishment and development of the educational partnership.